MODEL PROGRAM PEMBERDAYAAN EKONOMI DOMPET SOSIAL MADANI DALAM MEMBERDAYAKAN EKONOMI MASYARAKAT MUSLIM MELALUI PENGELOLAAN DANA ZAKAT,INFAQ DAN SHADAQAH (ZIS) - Desy Intan Normalasari; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This research aims to find out how economic empowerment program model of Dompet Sosial Madani goes on in empowering the economy of benefit recipients by funds management of zakat, infaq, and shadaqah.This research used qualitative-descriptive approach using case study strategy. Data collecting technique used is direct observation and being in the field of research. The results of the research shows that DSM did an accompaniment to the benefit recipients, while most of the assistances used infaq and shadaqah funds. The recipients accepted the assistances of business capital or business tools. By this existing program, the recipients hopefully will be able to empower themselves from being helpless to being useful to reach independency and welfare of their families.Keywords: LAZ, Zakat, Productive Zakat, Empowerment ModelREFFERENCESAdi,Isbandi, Rukminto. 2008. Intervensi Komunitas Pengembangan Masyarakat Sebagai Upaya Pemberdayaan Masyarakat. Jakarta:PT. Raja Grafindo Persada.Ali, Nuruddin, 2006, Zakat Sebagai Instrumen Dalam Kebijakan Fiskal, Jakarta, RajaGrafindo Persada.Amiruddin et al. Anatomin Fiqh Zakat. Yogyakarta : Pustaka Pelajar, 2005.Atmosudirjo, Wursanto, 2005.Dasar-DasarIlmuOrganisasi. Yogyakarta:Andi. Baznas (online) http://pusat.baznas.go.id/wp-content/perpu/UndangUndang%20No%2023%20Tahun%202011%20tentang%20Pengelolaan%20Zakat.pdf  20 january 2018 pkl 1.10pm).Bps Provinsi Bali, (online) (https://bali.bps.go.id/dynamictable/2016/07/19/33/jumlah-dan-persentase-penduduk-miskin-di-provinsi-bali-2012---2016.html  20 januari 2018 pkl 2.39pm)Cnn Indonesia, (online) (https://www.cnnindonesia.com/gaya-hidup/20170421134200-307-209237/bali-terima-penghargaan-destinasi-wisata-terbaik-di-dunia 20 january 2018 pkl 2.16pm)Dompet Sosial Madani Denpasar (online) (https://dompetsosial.id/artikels/kemenag-ri-sahkan-dompet-sosial-madani-bali-sebagai-laz-provinsi 20 january 2018 pkl 1.15pm)Fauzia, Amelia. 2008. Faith and a State: a History of Islamic Philanthropy in Indonesia.     Disertasi tidak diterbitkan. Melbourne Faculty of Arts University of Melbourne.Hadi, AgusPurbathin. 2004. KonsepPemberdayaan, PartisipasidanKelembagaandalam Pembangunan. YayasanAgribisnis/PusatPengembanganMasyarakatAgrikarya (PPMA).Huda, Nurul, dkk. 2012. Kebijakan Publik Islami. Jakarta: Kencana Prenada Media Group.Ife, Jim. 2002. Community Development (Sydney: Pearson Education Australia Pty Ltd.Kamil, Syukron. 2016. Ekonomi Islam, Kelembagaan, dan Konteks Keindonesiaan. Depok: PT Rajagrafindo Persada.Mahendrawaty, Nanih. 2001. Pembangunan Masyarakat Islam dari Ideologi, strategi, sampai Tradisi. Jakarta: Remaja Rosda Karya.Mardi Yatma Hutomo, 2000. Pemberdayaan Masyarkat dalam Bidang Ekonomi : Tinjauan Teoritik dan Implementasi, Working Paper.Muhammad & Abu Bakar HM, 2011. Manajemen Organisasi Zakat, Malang: Madani.Qardhawi, Yusuf. 1988. Fiqh al-Zakah. Bogor : Pustaka Lintera Antar NusaQardhawi, Yusuf. 1996. Hukum Zakat. Bogor: Pustaka Lintera Antar Nusa.Republik Indonesia. Undang-Undang No 38 Tahun 1999 tentang Pengelolaan Zakat. 1999: Kementerian Agama. ---------------------------. Undang-Undang No 23 Tahun 2011 tentang Pengelolaan Zakat. 2011: Diperbanyak oleh BAZNASRyandono, Muhammad Nafik Hadi. 2008 Ekoomi ZISWAF (Zakat, Infaq, Shadaqah dan Wakaf). Surabaya: Ifdi dan CenforisSekaran, Uma. 2006. Research Methods for Business. Edisi Terjemahan Jilid I. Jakarta: Salemba EmpatSugiyono. 2011. Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: AfabetaSuharto, Edi. 2009. Membangun Masyarakat Memberdayakan Rakyat. Bandung: PT. Refika Aditama Yin, Robert K. 2014. Study Kasus : Desain dan Metode, Terjemahan. Jakarta: PT Grafindo PersadaYin, Robert K. 2009. Case Study Research Design and Methods Fourth Edition. California:Sage Inc. http://kinekun.com/store/mengukur-kesejahteraan-joseph-e-stiglitz-amartya-senjean-paul-fitoussifile:///C/User/microsoft/Download/444-935-1-SM%20.pdf